The three billy goats gruff - Barnett, Mac (Orchard Books, an imprint of Scholastic Inc., 2022)
Once there was a bridge and a terrible and VERY hungry troll lived underneath it. When the three Billy Goats Gruff decide to clip-clop across the bridge to get to the grassy ridge, the troll is already imagining all the way to prepare a delicious goat dinner. But the troll underestimates those seemingly sweet but oh-so-savvy goats!